Strategic management of transport cargo complex - Okorokov, A. M. (Science and Transport Progress, 2014)
Purpose. Making the qualitative administrative decisions defining strategy and tactics of transport cargo complexes development, and also its subsystems, is possible only in the presence of flexible optimization model. This model has to consider multiparametricity and multicriteriality of the given task, uncertainty and vagueness of input information, and also to provide process automation of searching the best parameters of the given production facility. The purpose of the research is to develop procedures for the strategic management of complex with view of the most important factors and their stochastic nature, which will execute the improvement of technical equipment of TCC. Methodology. The problem of strategic management is based on solving the complex of issues of the optimal number of shunting locomotives, optimal processing capability of handling the front and rational capacity of warehouses. The problem is solved on the basis of the proposed optimality criterion – the specific set of profit per unit of capital assets of freight industry. The listed problems are solved using simulation modeling of the freight industry. Findings. The use of developed procedure allows one to improve the technical equipment of the freight stations and complexes. Originality. For the first time it was developed the procedure of strategic management of development. This procedure allows taking into account the probabilistic nature of demand for services of transport freight complexes and technological processes of client services on the complex stations. The proposed procedure can be applied during when planning the investments in the creation of transport freight complexes. Practical value. Use as a basic tool of simulation models of complex cargo operation allows estimating the effectiveness of the capital investments, the level of operating costs, as well as the quality of meeting the demands of potential customers in transportations at the stage of transport cargo complex.